Sains dan Etika dalam Dunia Digital: Menjaga Moralitas di Era Kecerdasan Buatan - Wulan, Sekar; Hanifah, Misulah; Restiansyach, Rieska (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
The rapid advancement of Artificial Intelligence (AI) in the digital age presents significant ethical challenges, particularly regarding human morality and responsibility. This study investigates the intersection between science and ethics in managing moral behavior in the AI era. The objective is to explore how ethical frameworks can be integrated into digital technologies to ensure moral accountability. A qualitative method was employed through literature analysis and expert interviews to gather relevant data. The findings reveal a growing concern among scholars and technologists about the absence of clear ethical boundaries in AI development and deployment. The study emphasizes the need for interdisciplinary collaboration to develop digital ethics guidelines. The impact of this research lies in proposing strategic approaches to embed ethical considerations into AI systems, thereby promoting responsible innovation. In conclusion, maintaining human morality within AI systems is crucial, and a balanced synergy between science and ethics is essential to guide future technological evolution.